Challenges of People With Reduced Mobility: The Angola and Brazil Study - Francisco, Aldino Miguel; Camoli , Horácio Cinco (Technical and Scientific Journal Green Cities, 2021)
People with disabilities in order to carry out their mobility activities have to live in an inclusive society as guided by the provisions of the “principle of equality, the law of persons with disabilities and the law of accessibility. The objective is to make a comparative analysis of Angolan and Brazilian legislation on people with disabilities or reduced mobility, taking as a case study four schools in the municipality of Moçâmedes (Angola). The main methods were bibliographic research, observation, photographic survey, systematization and analysis of the results of the qualitative material of the surveys was carried out with the aid of descriptive and percentage statistics, the criteria for assessing accessible and non-accessible environments were based on ABNT NBR 9050: 2020. It is concluded that the rules on accessibility in the two countries differ in the form of production, in Angola it is only national, and they are similar in the technical content and scope of application that are based on the municipalities. The items identified as having the greatest accessibility problems in schools were: Type of floor, Signage and Sanitary. In general, schools do not have an international symbol of accessibility or access routes, the material of the type of floor used and the toilets are not adapted for the disabled. The analyzed schools none are 100% adapted according to ABNT NBR 9050, since the accessibility assessment was the highest percentage of School 1 with 50% Accessibility, however, it was recommended to develop short and medium term infrastructure restructuring projects. school for greater inclusion. Keywords: Spatial accessibility. People with Reduced Mobility. Social inclusion.